Identification of Candida albicans by using different culture medias and its association in potentially malignant and malignant lesions - Sonal Saigal; Ankur Bhargava; S K Mehra; Falguni Dakwala (Wolters Kluwer Medknow Publications, 2011)
Background and Objective: The present study evaluates the association of Candida albicans with normal control group, potentially malignant and malignant lesions of oral cavity by using two different liquid culture media. Materials and Methods: Saliva was collected and biopsy was taken only from those clinically suspected potentially malignant and malignant lesions for histopathological diagnosis. Saliva samples were inoculated for fungal growth in Sabouraud's dextrose agar and culture-positive samples had undergone for Germ tube test. Germ tube-positive samples were further taken for quantification of chlamydospore production in liquid media at 8 and 16 hours. Results: In normal control groups no fungus growth was found; however, potentially malignant and malignant cases showed fungus growth, positive germ tube test and chlamydospore formation. The result also showed rapid and quantitatively more chlamydospore formation in corn meal broth + 5% milk in comparison to serum milk culture media. Conclusion: The oral mucosa is compromised in potentially malignant lesions, it can be argued that this species may be involved in carcinogenesis by elaborating the nitrosamine compounds which either act directly on oral mucosa or interact with other chemical carcinogens to activate specific proto-oncogenes and thereby initiate oral neoplasia.